The mechanisms and control strategies for quality deterioration in surimi gel during freeze-thawing cycles - Qiaoli Zhao; Bin Zheng; Yongqin Gao; Enlin Li; Xinyue Huo; Xue’er Li; Mi Zhang; Saiyi Zhong (Food Science of Animal Products)
Freezing is the primary preservation method for surimi gel. However, repeated freezing and thawing during storage, processing, or consumption can cause ice crystal growth and recrystallization, leading to mechanical damage to muscle cells and tissue. Additionally, it can induce protein denaturation and oxidation, ultimately resulting in a decline in the quality of surimi gel. This includes moisture loss, nutrient depletion, as well as deterioration in taste and texture. Therefore, it is crucial to incorporate cryoprotectants or utilize innovative freezing/thawing technologies to enhance the quality of freeze-thawed surimi gel. This review aims to elucidate the mechanisms underlying the quality deterioration of surimi gel during freeze-thawing cycles, summarize changes in myofibrillar protein and alterations in surimi gel quality after freeze-thawing cycle treatment, and finally strategies for enhancing the quality of surimi gel throughout the freeze-thawing cycles are discussed. This review will offer valuable references for improving the stability of freeze-thawed surimi gel and provide insights into the development of novel cryoprotectants and freezing/thawing technologies.